The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.cell.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Cell Atlas of the Tumor and Immune Ecosystem of Human Breast Cancer

Abstract: Summary Breast cancer is a heterogeneous disease. Tumor cells and associated healthy cells form ecosystems that determine disease progression and response to therapy. To characterize features of breast cancer ecosystems and their associations with clinical data, we analyzed 144 human breast tumor and 50 non-tumor tissue samples using mass cytometry. The expression of 73 proteins in 26 million cells was evaluated using tumor and immune cell-centric antibody panels. Tumors displayed individuality in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
544
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 614 publications
(605 citation statements)
references
References 64 publications
25
544
1
2
Order By: Relevance
“…We identified about 25% of total immune cells infiltrating BCs as CD14 + TAMs that express variable levels of CD163, underlying the phenotypic heterogeneity in TAMs. Through high‐dimensional analysis approaches, several recent reports have uncovered TAM heterogeneity at the single‐cell level in distinct tumor types, including BC, clear cell renal cell carcinoma, melanoma and lung adenocarcinoma . These studies revealed a great variety of distinct phenotypic TAM subsets that co‐exist by sharing the expression of well‐established M1 and M2 markers.…”
Section: Discussionmentioning
confidence: 99%
“…We identified about 25% of total immune cells infiltrating BCs as CD14 + TAMs that express variable levels of CD163, underlying the phenotypic heterogeneity in TAMs. Through high‐dimensional analysis approaches, several recent reports have uncovered TAM heterogeneity at the single‐cell level in distinct tumor types, including BC, clear cell renal cell carcinoma, melanoma and lung adenocarcinoma . These studies revealed a great variety of distinct phenotypic TAM subsets that co‐exist by sharing the expression of well‐established M1 and M2 markers.…”
Section: Discussionmentioning
confidence: 99%
“…By compiling and then comparing the levels of expression of many proteins across multiple cell types, single-cell mass cytometry is a robust readout to clarify the differentiation of expression patterns in multiple immune cell types. 20,22,23,25 Our comprehensive single-cell analysis of tumor, nontumorous colorectal tissue and blood demonstrate that the immunosuppressive/exhausted T cells were recruited/induced by the tumor microenvironment, even at the early stage of tumor development. To improve the response of immunotherapy targeting immune checkpoints, it is important to reverse the immunosuppressive tumor microenvironment.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, a previous study found that patients with breast cancer exhibited most PD-1+ T cells within the CD8+ compartment, whereas the mean expression of PD-1 was higher in CD4+ than in CD8+ T cells. 25 The mean expression level of PD-1 and PD-1 T-cell frequency strongly correlated with CD4+ and CD8+ subsets, indicating that these cells originated from T-cell expansion (Fig. 3e).…”
Section: T-cell Phenotypes Associated With Immunosuppression At the Tmentioning
confidence: 84%
See 1 more Smart Citation
“…The outcome showed that programmed cell death‐ligand 1 positive (PD‐L1 + ) tumor‐associated macrophages and exhausted T cells were abundant in high‐grade ER + and ER − tumors. This comprehensive single‐cell atlas of breast tumor indicated the significance of ecosystem‐based patient classification for precision medicine approaches …”
Section: Applicationsmentioning
confidence: 99%